Model-based investigation into atmospheric freeze drying assisted by power ultrasound. (April 2015) - Santacatalina, J.V.; Fissore, D.; Cárcel, J.A.; Mulet, A.; García-Pérez, J.V.
Highlights: Atmospheric freeze drying of apple assisted by ultrasound was successfully modeled. The model was validated using samples of different size and geometry. Ultrasound increased by up to one order of magnitude the water vapor diffusivity. Statistical tests revealed that ultrasound was the most relevant kinetic factor. Abstract: Atmospheric freeze drying consists of a convective drying process using air at a temperature below the freezing point of the processed product, and with a very low relative humidity content. This paper focuses on the use of a simple one-dimensional model considering moving boundary vapor diffusion to describe the ultrasonic assisted atmospheric freeze-drying of foodstuffs. The case study is the drying of apple cubes (8.8 mm) at different air velocities (1, 2, 4 and 6 m/s), temperatures (−5, −10 and −15 °C), without and with (25, 50 and 75 W) power ultrasound application. By fitting the proposed diffusion model to the experimental drying kinetics, the effective diffusivity of water vapor in the dried product was estimated. The model was successfully validated by drying apple samples of different size and geometry (cubes and cylinders). Finally, a 2 3 factorial design of experiments revealed that the most relevant operating parameter affecting the drying time was the applied ultrasound power level.